2020
DOI: 10.3390/cells9071701
|View full text |Cite
|
Sign up to set email alerts
|

RNA Recognition and Immunity—Innate Immune Sensing and Its Posttranscriptional Regulation Mechanisms

Abstract: RNA acts as an immunostimulatory molecule in the innate immune system to activate nucleic acid sensors. It functions as an intermediate, conveying genetic information to control inflammatory responses. A key mechanism for RNA sensing is discriminating self from non-self nucleic acids to initiate antiviral responses reliably, including the expression of type I interferon (IFN) and IFN-stimulated genes. Another important aspect of the RNA-mediated inflammatory response is posttranscriptional regulation of gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 172 publications
(195 reference statements)
0
28
0
Order By: Relevance
“…When dsRNA binds to RIG-1 or MDA5, oligomerization of the RNA sensors occurs which leads to activation of MAVS. As a result, IRF3/7 along with NF-κB gets activated and Interferon production is induced ( Uehata and Takeuchi, 2020 ).…”
Section: Toll-like Receptors and Viral Infectionsmentioning
confidence: 99%
“…When dsRNA binds to RIG-1 or MDA5, oligomerization of the RNA sensors occurs which leads to activation of MAVS. As a result, IRF3/7 along with NF-κB gets activated and Interferon production is induced ( Uehata and Takeuchi, 2020 ).…”
Section: Toll-like Receptors and Viral Infectionsmentioning
confidence: 99%
“…The common ligands of TLR3 exist on poly(I:C), dsRNA viruses (e.g., rotavirus (RV), respiratory syncytial virus (RSV), murine cytomegalovirus (MCMV)), and single-stranded RNA (ssRNA) virus (e.g., West Nile virus (WNV)) (Alexopoulou et al, 2001;Topping and Kelly, 2019;Uehata and Takeuchi, 2020). A recent report showed that endothelial TLR3 could also detect extracellular dsRNA that is secreted from highly metastatic tumors (Tavora et al, 2020).…”
Section: Activation Of Tlr3mentioning
confidence: 99%
“…This implies that the ablation of the IFN-I signal did not induce blunted IFN-I production after JEV footpad inoculation and, rather, the magnitude of IFN-I (IFN-α/β) expression seemed to follow the degree of JEV replication because the replication of JEV was coupled to the expression levels of IFN-α/β. IFN-I (IFN-α/β) binds to a heterodimeric receptor (IFNAR) and mediates downstream pleiotropic functions of the canonical JAK-STAT signaling pathway [23,24]. This stimulation results in the induction of antiviral ISGs, induction of cell surface and cytosolic PRRs in antigenpresenting cells, and the regulation of cytokine and chemokine production [19].…”
Section: Ifn-i Signal Is Essentially Required For Quick Innate Ifn-i mentioning
confidence: 99%
“…Indeed, the critical role of IFN-I and its transcription factors (IRF3, IRF5, and IRF7) has been described in avivirus infection in vivo including WNV and DenV, but not JEV [20][21][22]. IFN-I secreted from infected cells binds in an autocrine and paracrine manner to a heterodimeric IFN-α/β receptor (IFNAR) on the surface of cells and mediates pleiotropic effects via canonical Janus kinase (JAK)-signal transducer and activator of transcription (STAT1/2) signaling pathway [23,24]. Phosphorylated STAT1/2 heterodimer associates with IRF-9 to form ISGF3 complexes, which results in the induction of antiviral IFN-stimulated genes (ISGs, e.g., Mx1, OAS, PKR, ISG49[IFIT3], ISG54[IFIT2], ISG56[IFIT1]) through its nuclear translocation and binding to IFN-stimulated responsive elements [19].…”
Section: Introductionmentioning
confidence: 99%